(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2025)
Objective: To evaluate surgical wound complications by comparing conventional dressings and incisional negative pressure therapy (NPT) in spinal surgeries. Method: This was a longitudinal, observational, exploratory, and retrospective study with a quantitative approach, including 50 patients treated with conventional dressings and 50 with incisional NPT, conducted between 2017 and 2021. Data collection involved the analysis of 25 variables, with statistical tests conducted using an alpha level (p-value) of 0.05 and a 95% confidence interval (CI). Results: The overall complication rate was 37%, with a higher incidence of exudate and suture dehiscence. Patients treated with conventional dressings experienced more complications during hospitalization (88.24%) compared to those in the NPT group, who had a higher proportion of complications after discharge (50%) (p = 0.03). No statistically significant differences were found for the other variables. The conventional group also showed a higher frequency of infection one year postoperatively (14% vs. 12.24%). Conclusion: Patients with neuromuscular scoliosis have high rates of surgical wound complications. NPT was associated with a reduction in surgical wound infection and high-volume exudate compared to conventional dressings, although these differences were not statistically significant. Expanding the study sample is necessary to confirm the efficacy and potential superiority of incisional NPT.